To compare the blood pressure and heart rate during course of various types of anesthesia in wistar rat: A novel experiences - Narayan, Jagdish; Kumar, Pradeep; Gupta, Ankit; Tiwari, Sunita (Asian Journal of Medical Sciences, 2018)
Background: Rats are commonly used animals in development of newer drugs, rectification of toxicity and to record the various alterations in physiological parameters following pharmacological and non pharmacological interventions. Aim and Objectives: The purpose of this study was to identify the best physiological window during anesthesia. Therefore, we compared the effect of anesthesia using combination of ketamine and xylazine (KX) and thiopental sodium (intraperitoneally) on blood pressure and heart rate in adult male Wistar rats. Material and Methods: Twelve, male Wistar rats with a mean body weight of 260 ± 15 g were acquired. Thiopental sodium and cocktail of ketamine and xylazine (KX) were administered (ip) in group- I and group-II respectively. The systolic blood pressure and heart rate was recorded in both the groups till the awakening phase. Results: We found that there was a constant SBP and HR in Ketamine/Xylezine groups that are from 30 to 90 minutes after injection of anesthesia while this window was not observed in thiopental group. Conclusion: Our study concludes that the best time to observe the effect of newer drug during period between 30- 90 minutes after anesthesia. Asian Journal of Medical Sciences Vol.9(6) 2018 37-39